Production of Hydroxymethylfurfural Derivatives From Furfural Derivatives via Hydroxymethylation - Lv, Xianqing; Luo, Xiaolin; Cheng, Xin; Liu, Jing; Li, Changzhi; Shuai, Li (Frontiers in Bioengineering and Biotechnology, 2022)
Hydroxymethylfurfural (HMF) derivatives such as 2,5-bis(hydroxymethyl)furan (BHMF) and furandicarboxylic acid (FDCA) are promising alternative of fossil-based diols and dicarboxylic acids for synthesis of polyesters such as polyethylene terephthalate (PET). However, high cost for preparing HMF from biomass discourages the commercialization of HMF-derived polyesters. Since producing furfural (FUR) from five-carbon sugars (e.g., xylose) via dehydration is an inexpensive and commercialized process, we herein reported a method to synthesize BHMF derivatives (5-(ethoxymethyl)furan-2-methanol (EMFM), 2,5-bis(hydroxymethyl)furan monoacetate (BHMFM) and 2,5-bis(hydroxymethyl)furan diacetate (BHMFD) from furfural derivatives, i.e., (2-(ethoxymethyl)furan (EMF) and furfuryl acetate (FA)). To avoid strong acid-induced side reactions (e.g., furan ring opening, condensation and carbonization), two reaction systems, i.e., a low-concentration HCl aqueous solution combined with formaldehyde and anhydrous acetic acid combined with paraformaldehyde, were found to be suitable for such a hydroxymethylation reaction and could lead to decent product yields. In order to improve the carbon utilization, condensed furanic byproducts were further converted into hydrocarbon fuels via a reported two-step hydrodeoxygenation (HDO) process. This study not only validates the possibility of synthesizing functional HMF derivatives (EMFM, BHMFM, and BHMFD) from commercially-available FUR derivatives (EMF and FA), but also provide a new way to transform condensed furanics to value-added hydrocarbon fuels.